Securing water for trees and people : possible avenues - Gracia, Carlos; Vanclay, Jerry; Daly Hassen, Hamed; Sabaté Jorba, Santiago; Gyenge, Javier Enrique (2017)
In the context of water scarcity, threats on forest survival in drier areas, and thus of inevitable trade-off between man and nature for the use of water, this section addresses three main questions of importance for foresters and land-use planners: a) Can vegetation (upper- and understorey) management techniques in existing forest ecosystems reduce water stress for trees? b) Can vegetation management and land-use planning increase the availability of blue water and green water for other uses than the forest? c) To what extent and in what conditions can green water be directed to tree plantations?